Central America Social Expenditures and Institutional Review : Panama - World Bank Group (World Bank, Washington, DC, 2016)
Panama has experienced impressive and significant economic growth, emerging as one of the better performers in Central America in recent years and one of the fastest growing economies worldwide. From 2003 to 2013, Panama has averaged an annual GDP growth rate of approximately 7 percent, surpassing the average GDP growth in Central America. It has also emerged as one of the fastest growing economies worldwide. Even during the economic crisis of 2008-2009, its economy continued to grow albeit at a lower rate. This note recommends that Panama prioritize three main aspects: a) improving the effectiveness of social public spending by further enhancing the pro-poor and pro-indigenous features of targeting mechanisms; b) reducing inefficiencies in the various sectors, for example, by improving the coordination between the Ministries of Education, Health, Social Development, and CSS to minimize duplication of efforts and resources; and c) strengthening planning, budgeting, and information tools and systems, legislation, and institutions to support implementation and track progress toward Government goals.